2015
DOI: 10.9775/kvfd.2015.13138
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye Yerli Koyun Irklarında CAST Genine Ait Genetik Çeşitliliğin Belirlenmesi

Abstract: The aim of this study is to determine the genetic variability of CAST gene in native sheep breeds of Turkey by PCR-RFLP method. Six different native sheep breeds; Kivircik, Imroz, Karayaka, Hemsin, Red Karaman and Karakul were used in this study. This study was the first report about CAST gene variation in Karayaka, Red Karaman and Hemsin sheep breeds. After DNA isolation and PCR amplification, RFLP was performed with MspI enzyme. Two alleles M (336bp and 286bp) and N (622bp) were identified on 2% agarose gel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
(21 reference statements)
1
2
0
Order By: Relevance
“…Both populations deviated from the HWE at the CAST gene locus. The findings in this study did not agree with work by Avanus (2015) Genotype AB frequency of 0.735 recorded in the Djallonké population for instance could be because 78.3% (36) of the animals sampled were from the Ejura Sheep Breeding Station where selection of breeding animals is based on individuals with high growth trait parameters (e.g., birth weight, weaning weight, etc.). This may have inadvertently led to a selection bias favouring the AB genotype, however, further studies on the association of these identified genotypes with growth traits is required.…”
Section: Calpastatin (Cast) Genecontrasting
confidence: 97%
“…Both populations deviated from the HWE at the CAST gene locus. The findings in this study did not agree with work by Avanus (2015) Genotype AB frequency of 0.735 recorded in the Djallonké population for instance could be because 78.3% (36) of the animals sampled were from the Ejura Sheep Breeding Station where selection of breeding animals is based on individuals with high growth trait parameters (e.g., birth weight, weaning weight, etc.). This may have inadvertently led to a selection bias favouring the AB genotype, however, further studies on the association of these identified genotypes with growth traits is required.…”
Section: Calpastatin (Cast) Genecontrasting
confidence: 97%
“…In the Stara Zagora sheep the frequency of the mutant allele N is 0.03, of the genotype MM -0.97 and of the heterozygous genotype MN -0.03 [16], while in the Breznik breed there was a higher diversity -the frequency of the allele N was 0.12, of the genotype MM -0.77 and of the heterozygous MN -0.23 [17]. In studies of thin-tailed Turkish sheep breeds Kivircik, Imroz, and Karayaka, a null frequency of the NN genotype was found similar to the results in the present study, and in the Imroz breed the frequency of the M allele was 0.96 and of the heterozygous MN genotype was also close to this established by us -0.07 [8].…”
Section: ноsupporting
confidence: 90%
“…One of the promising markers for growth intensity and meat quality in sheep is the calpastatin gene (CAST) [6,7]. The CAST gene is located at locus 5q15 on chromosome 5 of the sheep genome (Ovis aries L.), it is composed of 29 exons separated by introns and has a total size of 89553 bp [8]. Genetic polymorphism has been identified in the following regions: exon 1, exon 6, exon 12, intron 12, and domains II to IV of the CAST gene [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, calpastatin (CAST) has a remarkable impact on growth parameters and carcass features [60]. The structure and location of the CAST gene in sheep have been determined; its locus is on chromosome 5, has 29 exons, and measures 89,553 bp [61]. It has been established that sheep CAST gene variation affects both growth traits and meat qualities [62].…”
Section: Discussionmentioning
confidence: 99%